Fostering cultural participation to address youth disillusionment in the context of the European Capital of Culture : the case of Oulu2026 - Pekkarinen, Jenni (Taideyliopiston Sibelius-Akatemia, 2021)
In June 2021, the city of Oulu was selected to host the European Capital of Culture (ECoC) 2026. For the old technology city located in the remote, Northern corner of Europe, the designation offers a great opportunity to develop what Oulu2026 calls Cultural Climate Change. However, besides opportunities, the ECoC is also faced with new challenges brought about by the Covid-19 pandemic and the looming risk of youth disillusionment. This qualitatively driven mixed case study research focuses on the challenges and opportunities related to young adults’ cultural participation in Oulu2026. The aim of the study is to explore and understand if and how Oulu can address the risk of youth disillusionment by fostering cultural participation in the context of the ECoC project. The research pays special attention to questions of marginalisation and disadvantage, the importance of which is also highlighted by the ECoC initiative. The study adopts an interdisciplinary approach and operates mainly in the fields of cultural planning, cultural policy, and arts management. The primary data consists of a survey among young adults in the Oulu2026 region, three semi-structured interviews with representatives of Oulu2026 and the city of Oulu, and document analysis focusing on the Oulu2026 bid book. The findings suggest that youth disillusionment is a real issue in the Oulu2026 region and that a link between cultural participation and youth disillusionment exists. Oulu2026 was found to address and respond to many real and existing cultural participation challenges among young adults in the region. However, an awareness of the diverse diversity of young adults still appeared to be lacking. The study suggests enhancing a cultural citizenship approach to participation and embracing a pluralist and intersectionally aware approach at all stages of cultural planning processes.
Keywords: nuoret; kulttuuri; kulttuuri-identiteetti; kulttuuripalvelut; pandemiat; fi=taidehallinto|sv=Arts Management|en=Arts Management|